2018
DOI: 10.1111/ajt.14526
|View full text |Cite
|
Sign up to set email alerts
|

The duration of asystolic ischemia determines the risk of graft failure after circulatory-dead donor kidney transplantation: A Eurotransplant cohort study

Abstract: Circulatory death donor (DCD) kidney transplantations are steadily increasing. Consensus reports recommend limiting donor warm ischemia time (DWIT) in DCD donation, although an independent effect on graft outcome has not been demonstrated. We investigated death-censored graft survival in 18 065 recipients of deceased-donor kidney transplants in the Eurotransplant region: 1059 DCD and 17 006 brain-dead donor (DBD) kidney recipients. DWIT was defined as time from circulatory arrest until cold flush. DCD donation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 20 publications
6
46
0
Order By: Relevance
“…also suggested the influence of the WIT on the survival of DCD grafts . A recent Eurotransplant cohort study also supported the present findings that the duration of asystolic ischemia (donor WIT) determines the risk of graft loss from DCD …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…also suggested the influence of the WIT on the survival of DCD grafts . A recent Eurotransplant cohort study also supported the present findings that the duration of asystolic ischemia (donor WIT) determines the risk of graft loss from DCD …”
Section: Discussionsupporting
confidence: 89%
“…14 A recent Eurotransplant cohort study also supported the present findings that the duration of asystolic ischemia (donor WIT) determines the risk of graft loss from DCD. 19 Suntharalingam et al reported that in DCD donors, warm ischemia started at the moment of withdrawal of life support, as the cardiopulmonary function slowly deteriorated, and was evident at the time of circulatory arrest. The median agonal phase was reported to be approximately 36 min, ranging from 5 min to 3 days, although most centers abandon donation if circulatory arrest has not occurred within 1-2 h. 20 Below 4 h, the agonal phase duration does not seem to influence the transplant outcome.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Eurotransplant cohort study, in the 5 years of post‐transplant follow‐up, the longer the WIT is prolonged and the more the graft failure increases. Nevertheless, these results were obtained without reporting the use of organ preservation techniques for DCD .…”
Section: Discussionmentioning
confidence: 97%
“…In controlled donors after circulatory death (cDCD), the effects of warm ischemia during the hypotensive phase, exacerbated during cold ischemia, may result in a higher incidence of primary nonfunction and delayed graft function in kidney transplantation. 1 Notably, while cDCDs have WIT that can be estimated, the WIT is often inexact and extended in uncontrolled donors after circulatory death (uDCD), making assessment of organ injury difficult. Abdominal normothermic regional perfusion (nRP) with extracorporeal membrane oxygenation (ECMO) device has been proposed to restore blood after the determination of death.…”
Section: Introductionmentioning
confidence: 99%
“…bolic profiling during nRP in uncontrolled DCD in relation to WIT flow (median, IQR) (min) 8(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Low flow (median, IQR) (min) 100 Low flow post-ECG (median, IQR) (min) 20(5-67) Warm ischemic time (median, IQR) (min) 132 (127-145) F, females; IQR, interquartile range; M, males; SD, standard deviation. F I G U R E 2 Creatinine values (top), lactate (middle) and ph (bottom) values throughout the study period.…”
mentioning
confidence: 99%